Food Products Packaging: A Study of its Effects on Consumer Behaviour - Giri, Sunil; Sharma, Vishal (Indian Journal of Marketing, 2012)
Today, the role of packaging is more than just helping customers to carry their packages to home; now-a-days, packaging not only tells them about the product, but also acts as an advertising media. Packaging is a very good communication medium as it gets the attention of consumers & they can relate to the product easily. Different organizations use different packaging attributes like designs, symbols, messages, shapes & combining colours. So the importance of packaging as a vehicle of consumer communication and branding is necessarily growing. To have knowledge about consumer psychology is important; so that manufacturers understand how the consumers respond to their packages. Due to change in the life styles of consumers, the interest in packaging is growing among organizations; so packaging performs an important role in marketing communications, especially at the point of sale and could be treated as one of the most important factors influencing consumer’s purchase decision. This paper explores the different factors of packaging, which influences the consumer to go for the purchase of particular snacks in Jammu region in the current scenario.